Increased RhoA prenylation in the loechrig (loe) mutant leads to progressive neurodegeneration. - Mandy Cook; Priya Mani; Jill S Wentzell; Doris Kretzschmar (PLoS ONE, 2012)
The Drosophila mutant loechrig (loe) shows age-dependent degeneration of the nervous system and is caused by the loss of a neuronal isoform of the AMP-activated protein kinase (AMPK) γ-subunit (also known as SNF4Aγ). The trimeric AMPK complex is activated by low energy levels and metabolic insults and regulates multiple important signal pathways that control cell metabolism. A well-known downstream target of AMPK is hydroxyl-methylglutaryl-CoA reductase (HMGR), a key enzyme in isoprenoid synthesis, and we have previously shown that HMGR genetically interacts with loe and affects the severity of the degenerative phenotype. Prenylation of proteins like small G-proteins is an important posttranslational modification providing lipid moieties that allow the association of these proteins with membranes, thereby facilitating their subsequent activation. Rho proteins have been extensively studied in neuronal outgrowth, however, much less is known about their function in neuronal maintenance. Here we show that the loe mutation interferes with isoprenoid synthesis, leading to increased prenylation of the small GTPase Rho1, the fly orthologue of vertebrate RhoA. We also demonstrate that increased prenylation and Rho1 activity causes neurodegeneration and aggravates the behavioral and degenerative phenotypes of loe. Because we cannot detect defects in the development of the central nervous system in loe, this suggests that loe only interferes with the function of the RhoA pathway in maintaining neuronal integrity during adulthood. In addition, our results show that alterations in isoprenoids can result in progressive neurodegeneration, supporting findings in vertebrates that prenylation may play a role in neurodegenerative diseases like Alzheimer's Disease.